Prognostic significance of standardized uptake value on 18fluorine-fluorodeoxyglucose positron emission tomography/computed tomography in patients with nasopharyngeal carcinoma - Seyda Turkolmez; Sabire Aksoy; Elif Özdemir; Zuhal Kandemir; Nilüfer Yildirim; Atiye Özsavran; Mehmet Çetindag; Kenan Köse (World Journal of Nuclear Medicine)
The aim of this study was to investigate the prognostic significance of standardized uptake value (SUV) on 18 fluorine-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in patients with nasopharyngeal carcinoma (NPC). Thirty-four patients who have histologically proven NPC and underwent 18F-FDG PET/CT were included in this study. After 18F-FDG PET/CT, all the patients received radiation therapy and 32 of them received concomitant weekly chemotherapy. The maximum SUV (SUVmax) at the primary tumor and the SUVmaxof the highest neck nodes were determined. The SUVmax-T ranged from 5.00 to 30.80 (mean: 15.37 ± 6.10) and there was no difference between SUVmax-T values for early and late stages (P = 0.99). The SUVmax-N ranged from 3.10 to 23.80 (mean: 13.23 ± 5.76). There was no correlation between SUVmax-T and SUVmax-N (r = 0.111, P = 0.532). There was no difference between the SUVmax-T and the positivity of neck lymph nodes (P = 0.169). The ability of SUVmaks-N to predict stage was obtained by a receiver operating characteristic (ROC) analysis. The area under the curve is 0.856 and the best cut-off value is 7.88. There was a good correlation between SUVmax-N and stage. While the mean SUVmax-T for the alive patients was slightly lower than that for the dead (14.65 ± 5.58 vs. 20.30 ± 7.92, P = 0.061), the difference between the groups was not statistically significant. Furthermore, there was no statistically significant difference for SUVmax-N between these two groups (P: 0.494). Cox-regression analysis showed that an increase in SUVmax-T and SUVmax-N was associated with death risk (relative risk [RR]: 1.13, P = 0.078 and RR: 1.052, P = 0.456, respectively). SUVmax-T and SUVmax-N were independent prognostic factors for survival in NPC patients. This will help the clinicians in choosing suitable candidates for more aggressive treatment modalities.